Asphalt pavement structure with uniform heat distribution and preparation method of each layer material

By combining a cooling top layer, a high thermal conductivity middle layer, and a heat-absorbing bottom layer, the road structure solves the problem of uneven temperature in asphalt pavement during high-temperature seasons, achieving uniform heat distribution and cooling effect, reducing high-temperature damage, and mitigating the urban heat island effect.

CN111851195BActive Publication Date: 2025-01-28NANJING FORESTRY UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202010853783.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-08-21
Publication Date
2025-01-28
Estimated Expiration
2040-08-21

AI Technical Summary

Technical Problem

The uneven temperature distribution of existing asphalt pavements during hot seasons leads to frequent rutting and other defects. Existing material optimization and coating-based cooling methods have limited effectiveness, are costly, and have unstable thermal conductivity.

Method used

The road structure consists of a cooling top layer, a high thermal conductivity middle layer, and a heat-absorbing bottom layer. These layers are composed of colored drainage asphalt mixture, crushed copper slag, a high thermal conductivity structural layer of alumina, and composite phase change materials. The uniform heat distribution is achieved through the functional combination of each layer.

Benefits of technology

It achieves uniform distribution of road surface temperature, reduces the occurrence of high-temperature diseases, alleviates the urban heat island effect, lowers road surface temperature, and improves rutting resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111851195B_ABST
    Figure CN111851195B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of pavement structure, and provides an asphalt pavement structure with uniform heat distribution and a method for preparing each layer of material, which includes, from top to bottom, a cooling upper layer, a high thermal conductivity middle layer, and a heat absorbing lower layer; the cooling upper layer is a colored drainage asphalt mixture layer with a thickness of 3 to 5 cm, the high thermal conductivity middle layer is a high thermal conductivity structural layer containing crushed copper slag and aluminum oxide, with a thickness of 5 to 7 cm; the heat absorbing lower layer is a heat absorbing structural layer containing a composite phase change material, with a thickness of 7 to 9 cm. The present invention is composed of structural layers with different functions, forming a linkage, which can actively adjust the temperature field, make the heat evenly distributed inside the structure, reduce the temperature difference between each layer, fundamentally reduce the occurrence of high temperature diseases, and alleviate the urban heat island effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of road engineering, and in particular relates to an asphalt pavement structure with uniform heat distribution and a preparation method of each layer of materials. Background Art

[0002] High temperature damage is one of the main forms of damage to asphalt pavement. Studies have shown that when the road surface temperature reaches 55-60°C, rutting will develop at a centimeter-level speed. Asphalt pavement is black, has a high heat absorption rate, and is mostly made of densely mixed asphalt mixtures, which are easy to absorb heat but difficult to release heat, making high temperature damage frequent in summer.

[0003] At present, the main way to deal with high-temperature diseases of asphalt pavements is to optimize materials, such as using high-modulus asphalt, adding fibers, anti-rutting agents, etc., or adjusting the gradation of the mixture. However, due to the large heat absorption of black asphalt pavements, the performance improvement is limited, and the problem has not been fundamentally solved. Light-colored reflective coatings, thermal resistance asphalt mixtures, etc., reduce the temperature of the road structure, but the temperature of pure coating or thermal resistance pavements is still high during the high temperature period in summer, and durability and cost are important factors restricting its development. In recent years, many scholars have also studied the heat-conducting asphalt pavement structure layer, but the heat conduction direction is not single-phase transmission, but transmission to the surroundings. Therefore, the heat conduction capacity of the heat-conducting pavement structure layer is relatively unstable downward, and further improvement is needed to accelerate the stability and rate of heat conduction. The temperature of the internal structure of the pavement gradually decreases from top to bottom, and the temperature distribution is very uneven. In the hot season, the road surface temperature can reach above 70°C, the middle surface layer temperature is about 56°C, and the lower layer temperature is 45-50°C. The road surface absorbs a large amount of solar radiation, resulting in a high temperature. The temperature of the middle surface layer, which is prone to rutting, is also high. The temperature difference between the lower layer and the middle and upper layers is large, and the heat distribution is uneven.

[0004] Therefore, it is an urgent problem to utilize pavement materials with good performance and low cost, and to reasonably combine pavement structure layers with different functions to produce an asphalt pavement structure with good cooling, fast and stable heat conduction, and uniform heat distribution. Summary of the invention

[0005] The purpose of the present invention is to address the above problems and provide an asphalt pavement structure with uniform heat distribution and active cooling, and a method for preparing the materials of each layer thereof, wherein the raw materials are widely available and inexpensive, and the structural distribution of each layer is reasonable, so that the temperature of the pavement structure is reduced, the temperature difference of each layer is small, and the heat is evenly distributed.

[0006] The principle of the present invention is: an asphalt pavement structure with uniform heat distribution, characterized in that: from top to bottom, it includes a cooling upper layer, a high thermal conductivity middle layer and a heat absorbing lower layer; the cooling upper layer is a colored drainage asphalt mixture layer with a thickness of 3 to 5 cm, the high thermal conductivity middle layer is a high thermal conductivity structural layer containing crushed copper slag and aluminum oxide, with a thickness of 5 to 7 cm; the heat absorbing lower layer is a heat absorbing structural layer containing a composite phase change material, with a thickness of 7 to 9 cm.

[0007] The present application also discloses an asphalt pavement structure with uniform heat distribution and a method for preparing materials of each layer, which is applicable to the above-mentioned pavement structure, and is characterized in that: the method for preparing the material of the cooling upper layer comprises the following steps:

[0008] Step 1: Heat the basalt aggregate, decolorized asphalt and mineral powder to 180℃, and preheat the mixing pot to 180℃.

[0009] Step 2: Put basalt aggregate, SBS modifier and high viscosity modifier into a mixing pot and stir for 90 seconds.

[0010] Step 3: Pour decolorized asphalt into the mixing pot and stir for 90 seconds.

[0011] Step 4: Add mineral powder and color powder and stir for 90 seconds to make a colored drainage asphalt mixture, followed by paving and rolling the cooled top layer.

[0012] The technical solution further defined in the present invention is as follows: the raw material composition of the cooling top layer and its total weight ratio to the colored asphalt mixture are 88%-92% basalt, 3%-6% mineral powder, 0.5%-1% toner, 3.5%-5.5% decolorized asphalt, 0.15%-0.4% SBS modifier, 0.25%-0.85% high viscosity modifier and 0.1%-0.3% fiber.

[0013] Preferably, the high thermal conductivity middle surface layer adopts AC-20 grading. The copper slag is first crushed, and six grades of materials of 19mm, 16mm, 4.75mm, 2.36mm, 0.075mm and 0.15mm are collected after screening, and the aggregates of the corresponding particle size are replaced by equal volumes.

[0014] Preferably, the high thermal conductivity middle surface layer further comprises 200-300 mesh basic alumina powder.

[0015] Preferably, the heat-absorbing lower layer is made of a prepared composite phase change material, the composite phase change material uses expanded vermiculite as a packaging matrix, and is acidified and modified with 0.05 mol / L HCL, Na2SO4·10H2O or MgSO4·7H2O is selected as a phase change material, and is modified with 5% borax as a nucleating agent, and epoxy resin is used as a sealing agent, and the mass ratio of the three materials Na2SO4·10H2O or MgSO4·7H2O, expanded vermiculite and sealing agent is 25-30:10-15:1.

[0016] Preferably, the preparation of the composite phase change material comprises the following steps:

[0017] The first step is to weigh Na2SO4·10H2O or MgSO4·7H2O crystals, add borax of 5% of the mass of Na2SO4·10H2O or MgSO4·7H2O crystals, and place them in a blast oven at 40°C for 48 hours for modification;

[0018] The second step is to put the expanded vermiculite into 0.05 mol / L HCL, heat it in a water bath at 65°C and stir it for 2 hours, then wash it with deionized water and dry it to obtain modified expanded vermiculite.

[0019] The third step is to add modified Na2SO4·10H2O or MgSO4·7H2O into deionized water to prepare a saturated solution, then add modified expanded vermiculite, stir at 1000 rpm for 2 h, and impregnate under vacuum pressure at 65 °C for 6 h;

[0020] The fourth step is to obtain the product obtained in the third step, add epoxy resin as a sealing agent, stir for 6 hours, air-dry and grind to obtain an expanded vermiculite-based Na2SO4·10H2O or MgSO4·7H2O composite phase change material.

[0021] The beneficial effects of the present invention are as follows: (1) The present invention is composed of structural layers with different functions, forming a linkage that can actively adjust the temperature field so that heat is evenly distributed inside the structure. The temperature difference between the layers is small, which fundamentally reduces the occurrence of high temperature diseases and alleviates the urban heat island effect. (2) The cooling upper layer of the present invention is light in color and has a high porosity, so it has a low heat absorption rate and can dissipate heat quickly. (3) The high thermal conductivity middle layer of the present invention is added with high thermal conductivity materials to improve the thermal conductivity, so that the heat of the middle and upper layers is quickly transferred to the lower layer, thereby improving the anti-rutting ability. (4) The heat-absorbing lower layer of the present invention can accelerate and stabilize the ability of the middle and upper layers to transfer heat downward, and the internal phase change material can reduce or delay the occurrence of high temperature peaks. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Schematic diagram of the pavement structure of the present invention. DETAILED DESCRIPTION

[0023] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments.

[0024] like Figure 1 As shown, the present invention is further described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0025] The pavement structure in this embodiment includes a cooling upper layer 1, a high thermal conductivity middle layer 2 and a heat absorbing lower layer 3 from top to bottom. The cooling upper layer is a colored drainage asphalt mixture layer with a thickness of 3 to 5 cm, the high thermal conductivity middle layer is a high thermal conductivity structural layer containing crushed copper slag and aluminum oxide, with a thickness of 5 to 7 cm; the heat absorbing lower layer is a heat absorbing structural layer containing composite phase change materials, with a thickness of 7 to 9 cm. The pavement structure of this embodiment improves the problem of large temperature difference between pavement structural layers under high temperature, so that the upper layer with higher temperature absorbs less heat, and the middle layer conducts heat to the lower layer with lower temperature. The lower layer has a certain heat absorption capacity, which can accelerate and stabilize the downward conduction of the temperature of the middle and upper layers, and promote the directional heat conduction from top to bottom, rather than free heat conduction without direction, reducing the structural layer diseases caused by high temperature in the middle and upper layers. Through the combination of structural layers with different functions, the heat of each layer is evenly distributed, the temperature field is adjusted, the temperature difference of each layer is reduced, and the urban heat island effect is alleviated.

[0026] Table 1 AC-25 gradation

[0027]

[0028] This embodiment is paved and rolled from bottom to top. The heat-absorbing lower layer adopts AC-25 grading, the stone material is basalt, the grading is shown in Table 1, and modified asphalt is used, with an oil-stone ratio of 4.2%. The thickness is 7 to 9 cm. In the asphalt mixture, an equal volume of expanded vermiculite-based Na2SO4·10H2O composite phase change material is used to replace 0.075-0.6mm particle size aggregate and 60% of mineral powder. The mass ratio of Na2SO4·10H2O, expanded vermiculite, and sealing agent is 25 to 30:10 to 15:1.

[0029] The preparation steps of expanded vermiculite-based Na2SO4·10H2O composite phase change material are as follows:

[0030] In the first step, 200 g of Na2SO4·10H2O crystals were weighed, 5% of the mass of Na2SO4·10H2O crystals of borax was added, and the mixture was placed in a 40°C forced air oven for 48 h to obtain a total of 210 g of borax-modified Na2SO4·10H2O.

[0031] In the second step, 105 g of expanded vermiculite was put into 400 ml of 0.05 mol / L HCL, and placed in a 65° C. water bath for heating and stirring for 2 h, and then washed with deionized water and dried to obtain modified expanded vermiculite.

[0032] In the third step, the modified Na2SO4·10H2O was added into deionized water to prepare a saturated solution, and then the modified expanded vermiculite was added, stirred at 1000 rpm for 2 h, and impregnated under vacuum pressure at 65°C for 6 h.

[0033] The fourth step is to obtain the product obtained in the third step, add a sealing agent, stir for 6 hours, air-dry, and grind to obtain an expanded vermiculite-based Na2SO4·10H2O composite phase change material.

[0034] The fifth step is to screen the obtained expanded vermiculite-based Na2SO4·10H2O composite phase change material.

[0035] Table 2 AC-20 gradation

[0036]

[0037] In this embodiment, the high thermal conductivity middle surface layer adopts AC-20 grading with a thickness of 5 to 7 cm, and the aggregate is basalt, with a grading as shown in Table 2, and the oil-stone ratio is 4.3%. Among them, the six grades of 19mm, 16mm, 4.75mm, 2.36mm, 0.075mm and 0.15mm are crushed copper slag with equal particle size to replace the original aggregate of equal volume, and 300 mesh basic alumina powder is mixed into the asphalt mixture in an equal volume instead of mineral powder at a ratio of 60%. The middle surface layer uses high thermal conductivity materials such as copper slag and alumina to improve thermal conductivity and accelerate the temperature conduction to the lower part.

[0038] Table 3 PAC-13 gradation

[0039]

[0040] The cooling top layer in this embodiment uses a colored asphalt mixture, and the cooling top layer in this embodiment uses a PAC-10 or PAC-13 grading, as shown in Table 3, with a thickness of 3 to 5 cm, and the fraction of each raw material in the total weight of the colored asphalt mixture is: basalt accounts for 91.3%, modified asphalt accounts for 4.5%, and mineral powder accounts for 4%. The preparation method includes the following steps:

[0041] The first step is to heat the basalt, mineral powder and decolorized asphalt to 180℃, and preheat the mixing pot to 180℃;

[0042] In the second step, basalt, SBS modifier and high viscosity modifier were put into a mixing pot and stirred for 90 seconds.

[0043] Step 3: Pour decolorized asphalt into the mixing pot and stir for 90 seconds;

[0044] The fourth step is to add limestone powder and color powder and stir for 90 seconds to make a colored drainage asphalt mixture, followed by paving and rolling the cooling top layer.

[0045] As a preferred embodiment of this embodiment, the modified asphalt comprises decolorized asphalt, SBS modifier and high viscosity modifier, wherein the SBS modifier and the high viscosity modifier account for 8% and 5% of the total weight of the asphalt, respectively.

[0046] As a preferred embodiment of the present invention, the mineral powder comprises red iron oxide powder and limestone mineral powder, which account for 15% and 85% of the total mass of the mineral powder respectively.

[0047] As a preference of this embodiment, the fibers account for 0.2% of the total mass of the colored drainage asphalt mixture.

[0048] Preferably, a waterproof adhesive layer with a thickness of 1-4 mm is laid on the lower part of the cooling upper layer to prevent water from seeping downward.

[0049] Preferably, MgSO4·7H2O composite phase change material may be used to replace Na2SO4·10H2O in the composite phase change material, and other materials and preparation methods remain unchanged.

[0050] In this embodiment, the cooling upper layer has a large porosity and a lower heat absorption rate than the black asphalt pavement, so that the road surface temperature is relatively low; the high thermal conductivity middle surface layer enhances the thermal conductivity of the structural layer, so that the temperature of the middle and upper layer can be quickly transferred downward; due to the large temperature difference between the upper and lower layers, the heat-absorbing lower layer improves its heat absorption capacity by adding a composite phase change material, absorbs excess heat from the middle and upper layer, accelerates and stabilizes the downward conduction of heat from the middle and upper layer, and keeps the temperatures of each surface layer similar; at the same time, due to the properties of the composite phase change material itself, it can absorb and store heat, delay the occurrence of the high-temperature peak of the lower layer, and prevent high-temperature diseases in the middle and lower layers to a certain extent.

[0051] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements without departing from the principle of the present invention. These improvements should also be regarded as within the scope of protection of the present invention.

Claims

1. An asphalt pavement structure with uniform heat distribution, characterized in that: From top to bottom, it includes a cooling upper layer, a high thermal conductivity middle layer and a heat absorbing lower layer; the cooling upper layer is a colored drainage asphalt mixture layer with a thickness of 3 to 5 cm, and the raw materials of the colored drainage asphalt mixture layer include basalt, modified asphalt and mineral powder, and the fraction of each raw material in the total weight of the colored asphalt mixture is as follows: basalt accounts for 91.3%, modified asphalt accounts for 4.5%, and mineral powder accounts for 4%; the high thermal conductivity middle layer is a high thermal conductivity structural layer containing crushed copper slag and aluminum oxide, with a thickness of 5 to 7 cm; the heat absorbing lower layer is a heat absorbing structural layer containing composite phase change material, with a thickness of 7 to 9 cm; a waterproof adhesive layer is laid on the lower part of the cooling upper layer, with a thickness of 1 to 4 mm.

2. A method for preparing materials for each layer of an asphalt pavement structure with uniform heat distribution, applicable to the pavement structure according to claim 1, characterized in that: The material preparation method of the cooling top layer comprises the following steps: Step 1: Heat the basalt aggregate, decolorized asphalt and mineral powder to 180℃, and preheat the mixing pot to 180℃. Step 2: Put basalt aggregate, SBS modifier and high viscosity modifier into a mixing pot and stir for 90 seconds. Step 3: Pour decolorized asphalt into the mixing pot and stir for 90 seconds. Step 4: Add mineral powder and color powder and stir for 90 seconds to make a colored drainage asphalt mixture, followed by paving and rolling the cooled top layer.

3. The method for preparing each layer material of asphalt pavement structure with uniform heat distribution according to claim 2, characterized in that: The raw material composition of the cooling top layer and its proportion in the total weight of the colored asphalt mixture are 88% to 92% basalt, 3% to 6% mineral powder, 0.5% to 1% toner, 3.5% to 5.5% decolorized asphalt, 0.15% to 0.4% SBS modifier, 0.25% to 0.85% high viscosity modifier and 0.1% to 0.3% fiber.

4. The method for preparing each layer material of an asphalt pavement structure with uniform heat distribution according to claim 3, characterized in that: The high thermal conductivity middle surface layer adopts AC-20 grading. First, the copper slag is crushed, and six grades of materials of 19mm, 16mm, 4.75mm, 2.36mm, 0.075mm and 0.15mm are collected after screening, and the aggregates of the corresponding particle size are replaced by equal volumes.

5. The method for preparing each layer material of asphalt pavement structure with uniform heat distribution according to claim 4, characterized in that: The high thermal conductivity middle surface layer also includes 200-300 mesh basic aluminum oxide powder.

6. The method for preparing each layer material of asphalt pavement structure with uniform heat distribution according to claim 5, characterized in that: The heat-absorbing lower layer uses a prepared composite phase change material, the composite phase change material uses expanded vermiculite as a packaging matrix, and is acidified and modified with 0.05 mol / L HCL, MgSO4·7H2O or Na2SO4·10H2O is used as a phase change material, and is modified with 5% borax as a nucleating agent, and epoxy resin is used as a sealing agent, and the mass ratio of the three materials Na2SO4·10H2O or MgSO4·7H2O, expanded vermiculite and the sealing agent is 25-30:10-15:

1.

7. The method for preparing each layer material of asphalt pavement structure with uniform heat distribution according to claim 6, characterized in that: The preparation of the composite phase change material comprises the following steps: The first step is to weigh Na2SO4·10H2O or MgSO4·7H2O crystals, add borax of 5% of the mass of Na2SO4·10H2O or MgSO4·7H2O crystals, and place them in a blast oven at 40°C for 48 hours for modification; The second step is to put the expanded vermiculite into 0.05 mol / L HCL, heat it in a water bath at 65°C and stir it for 2 hours, then wash it with deionized water and dry it to obtain modified expanded vermiculite. The third step is to add modified Na2SO4·10H2O or MgSO4·7H2O into deionized water to prepare a saturated solution, then add modified expanded vermiculite, stir at 1000 rpm for 2 h, and impregnate under vacuum pressure at 65°C for 6 h; The fourth step is to obtain the product obtained in the third step, add epoxy resin and stir for 6 hours, air-dry and grind to obtain expanded vermiculite-based Na2SO4·10H2O or MgSO4·7H2O composite phase change material.

Citation Information

Patent Citations

  • Process for producing stephanoporate composite inorganic phase-changing material

    CN101294064A

  • Anti-track bituminous pavement cooling structure and material composition of each layer thereof

    CN110499687A

  • Functional drainage pavement and preparation method thereof[v]

    CN111233375A

  • Phase change cooling bituminous pavement structure

    CN204212019U

  • Asphalt pavement structure with uniform heat distribution

    CN212477302U